Case Study of Modern and Postmodern Styles Impact on Administration Architecture in Independent Malaysia Since 20th to 21th Century - Yee, Chong Wei; Shukri, Sharyzee Mohmad; Aminuddin, A M R; Awaluddin, Zuraina Leily (MAJ - Malaysia Architectural Journal, 2021)
The main purpose is to expound the modern and postmodern architectural styles of administration architecture in Malaysia and outlined the possible causes that may influence the conception of these styles. Despite the fact that studies of administration architecture in other countries have revealed a relationship between administration architecture and politics as well as symbols of a certain race’s identity, no such studies that express administration architecture in Malaysia. The research on administrative architecture in Malaysia focuses on six main components: historical documentation, strategies of preserving and conserving past administrative buildings, documentation of administrative buildings in the form of measured drawings, and conversation of theory for designing administrative buildings in urban cities. A case study strategy, as outlined by Yin (1993), was used to collect data by using two significant case studies from different periods of Malaysian government (20th to current). In contrast to the three typical types of administrative architecture suggested by various historians, such as Colonial, and Modern styles, the research has identified two key styles with a recommendation of the reasoning and effects of those styles. The finding for practising architects to understand that the current syntax of ’administrative architecture,’ with its references in Middle Eastern and Western models, is not always the best precedent for projecting one’s nation’s architectural message due to country’s own identity and the value of regionalism.